ANTIPLATELET CONTROL OF VESSELS OVER THE MAIN BLOOD CELLS IN HYPERTENSIVES WITH DYSLIPIDEMIA IN COMPLEX THERAPY - I. A. Skorjatina; I. N. Medvedev; S. Yu. Zavalishina (Кардиоваскулярная терапия и профилактика)
The serious progress in dyslipidemia treatment (DL), incl. the cases of arterial hypertension (AH) comorbidity, has been statins introduction. It was found that the level of statins therapeutical effect grade significantly improves if there are hypolipidemic diet and tolerable exercises. However in this category of patients there was no assessment of the influence of the most active statins, including rosuvastatin (Rs) in combination with non-medication treatment, on the influence of antiaggregation properties of the vessels on the main blood cells.Aim. To assess in AH and DL patients, the opportunity of medical usage of the combination Rs with hypolipidemic diet and tolerable exercises, on antiplatelet properties of the vascular wall influence on erythrocytes, thrombocytes and neutrophils.Material and methods. Totally, 61 patients studied, with AH of 1-2 grades, risk 3, DL type IIb, middle age. Controls were 26 healthy persons of the same age. In the study, we used biochemical, hematological and statistical methods.Results. The enhancement of DL and AH patients aggregation of erythrocytes, thrombocytes and neutrophils, is mostly due to decreased antiplatelet control of vessel wall due to disorders of lipid metabolism, lipid peroxidation processes activation in plasma, decreased synthesis of nitric oxide and prostacyclin. As a result of the 6-month complex treatment, in AH with DL patients there is optimization of lipid content and of lipid peroxidation in plasma, with a 12-month achievement of complete normalization of antiplatelet abilities of vascular wall with its retention for at least 92 weeks of follow-up, if the therapy is continued.Conclusion. As a result of 1,5-month implementation of the complex treatment of AH and DL, there is optimization of lipid profile and peroxidation processes in plasma. Complete normalization of antiplatelet abilities of the vessel wall is reached by the 3rd moths with retention of the optimal values by the end of the study.